Bioorthogonal Radiopaque Hydrogel for Endoscopic Delivery and Universal Tissue Marking. Issue 4 (20th December 2015) - Hong, Seonki; Carlson, Jonathan; Lee, Hakho; Weissleder, Ralph
Abstract : A novel dual marking hydrogel system is reported for radiological and laparoscopic localization of lesions. Bioorthogonally crosslinked hydrogel containing both tantalum and India ink can be rapidly formed inside the body after injecting precursors, and stably located for several days as a long‐term biocompatible carrier for markers.